The Effect of risk management on financial Performance in Uganda. A Case of Kabale Municipal Council, Kabale District. - Kabweine, Bernard Mwesigwa; Eton, Marus; Sunday, Arthur; Ogwel, Bernard Patrick (Kabale University, 2023)
To examine the effect of risk management on financial performance in Uganda. We explored literature on risk management and the relationships with financial performance in public sector organizations. We designed a theoretical relationship between risk management and financial performance. A descriptive research design was adopted and a sample size of 169, which constituted council employees and beneficiaries was used. Data were collected through questionnaires and interviews. The study found a significant effect of risk management on financial performance. The study also established positive and significant relationships between risk management and financial performance at (r = .627; sig. <.05). Generally, risk management accounts for 39.3% of the total variations in the financial performance of Kabale municipality. The study shows that local governments in Uganda have strong risk management systems and are likely to register a 50% variation in their financial performance. The study recommends to both public and private organizations improve their risk management systems for high financial performance. The audit departments should strengthen risk management and control activities at the department level.